PERAWATAN HYBRID PROSTHESIS DENGAN PRECISSION ATTACHMENT PADA KASUS FRAKTUR GIGI TIRUAN TETAP - Rahardyan Parnaadji (Fakultas Kedokteran Gigi Universitas Jember, 2012)
Fixed partial dentures (FPD) have been shown to exhibit clinical complications due to a wide variety of factors. Commonly observed complications associated with a conventional FPD include loss of retention and tooth fracture. The hybrid prosthesis is one of several treatment option of case of fracture of fixed partial denture. The hybrid prosthesis could improve an aesthetic and masticatory functions because it use of precission attachment was to enhance denture retention.The aim of this case report paper was to explain the management of treatment of a hybrid prosthesis with precision attachment could improve an aesthetic and masticatory functions on case of fracture of fixed partial denture. The case study was carried out on a 55 year old female patient with case of fracture of fixed partial denture on tooth 25, 26 and 27. She needed more comfortable denture to improve her aesthetic and functional performance. A metal removable partial denture with female part placed within the tooth 25, 26 and 27 were designed to replace the posterior maxillary teeth. The male part of precission attachment placed on tooth 24. In conclusion, the hybrid prosthesis with precision attachment can enhance denture retention and stability and has no effect an aesthetic performance on case of fracture of fixed partial denture.